THE USE OF CODE-MIXING BY THE CASTER IN PUBG MOBILE TOURNAMENT â€œPMPL SEA FINALS SEASON 2â€ - Abdul Rozzaq Wijaya, Rahmaditya Khadifa; Hidayatullah, Aris; Mayangseto, Ginarsiwi (LPPM Universitas Duta Bangsa Surakarta, 2023)
This study aims to determine the types of code mixing and the factors that cause code mixing. The data in this study are the types of code mixing Inter Sentential Code Mixing and Inter Lexical Code Mixing. The source of the data in this study was the PUBG Mobile e-sport tournament video with the title